2014
DOI: 10.1371/journal.pone.0110879
|View full text |Cite
|
Sign up to set email alerts
|

Monocyte-Derived Dendritic Cells from Patients with Dermatophytosis Restrict the Growth of Trichophyton rubrum and Induce CD4-T Cell Activation

Abstract: Dermatophytes are the most common agents of superficial mycoses that are caused by mold fungi. Trichophyton rubrum is the most common pathogen causing dermatophytosis. The immunology of dermatophytosis is currently poorly understood. Recently, our group investigated the interaction of T. rubrum conidia with peritoneal mouse macrophages. We found that macrophages phagocytose T. rubrum conidia resulted in a down-modulation of class II major histocompatibility complex (MHC) antigens and in the expression of co-st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
20
0
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(23 citation statements)
references
References 24 publications
1
20
0
1
Order By: Relevance
“…While deficiencies in other PRRs also impair the fungal control and promote the infection-as we and others have previously shown for mannose receptor and DC-SIGN, 41 the NLRP3 inflammasome 17 and DC-HIL 42 -here we stress the great and cooperative contribution of Dectin-1 and Dectin-2 against this pathogen. Collectively, these works indicate that the immunity to T. rubrum is a complex, rather than a straightforward, framework that relies on multiple inputs for appropriate control and where individual interferences may compromise its performance.…”
Section: Discussionsupporting
confidence: 71%
See 1 more Smart Citation
“…While deficiencies in other PRRs also impair the fungal control and promote the infection-as we and others have previously shown for mannose receptor and DC-SIGN, 41 the NLRP3 inflammasome 17 and DC-HIL 42 -here we stress the great and cooperative contribution of Dectin-1 and Dectin-2 against this pathogen. Collectively, these works indicate that the immunity to T. rubrum is a complex, rather than a straightforward, framework that relies on multiple inputs for appropriate control and where individual interferences may compromise its performance.…”
Section: Discussionsupporting
confidence: 71%
“…Accordingly, HIV was shown to act directly on macrophages, compromising the signaling pathways of TLRs and Dectin-1. 30 Moreover, while lymphocytes from immunocompetent patients with dermatophytosis can proliferate in response to T. rubrum antigens and still show some fungicidal activity in vitro, 31,32 patient-derived dendritic cells are also able to induce T-cell proliferation, indicating normal antigen presentation and co-stimulatory capabilities, 33 and suggesting that dermatophytosis is not necessarily associated with depressed or altered adaptive immunity. Recently, Baltazar et al showed IL-12 and IFN-g responses are required to combat T. rubrum.…”
Section: Discussionmentioning
confidence: 99%
“…Santiago et al 18 Biopsy specimens from skin lesions Tissues from localized (LD) and disseminated (DD) dermatophytoses by T. rubrum Reduced TLR4 expression, but not TLR2 expression, was detected in both DD and LD patientscompared with the control group.…”
Section: T Mentagrophytes T Rubrum and T Tonsuransmentioning
confidence: 99%
“…For example, the models have shown that IFN-g, IL-12, IL-1b, and IL-17 are important cytokines for controlling T. rubrum infection and that skin lesions of patients present lower expression of Toll-like receptor 4 (TLR4) than that seen in the control groups. 1,17,8 Furthermore, both dendritic cells (DCs) and macrophages interact with T. rubrum conidia, 8,9,18 but Santiago et al 18 demonstrated that only DCs inhibited T. rubrum growth and induced Th activation, suggesting that these cells play an important role in coordinating the development of the cellular immune response during T. rubrum infection. In conclusion, much work is still required to provide scientific information about dermatophyte infections to a level at least similar to that for other fungal infections caused by species that are easier to manipulate (e.g., Candida and Cryptococcus).…”
Section: T Mentagrophytes T Rubrum and T Tonsuransmentioning
confidence: 99%
“…Assim, Rissoan et al (1999) (Cambi et al, 2003), Penicillium marneffei (Ngaosuwankul et al, 2008) e Trichophyton rubrum (Santiago et al, 2014).…”
mentioning
confidence: 99%